PENGARUH LAMA PENYIMPANAN TERHADAP STABILITAS FISIK DAN KIMIA LOTION PENUMBUH RAMBUT EKSTRAK BIJI KEMIRI (Aleurites moluccana L. Willd.) - Anas Putro Senu Prasojo; Sri Mulyani; Mufrod Mufrod (Faculty of Pharmacy, Universitas Gadjah Mada, 2012)
Etanolic extract 70% of candlenut which has 5% concentration have been reported to have hair restoring activity. This study aims to investigate the effect of length storage on physical stability and flavonoid content of hair restoring lotion candlenut extract so that produce an acceptable form. Lotion were made in variation of xanthan gum concentration 0.5%; 1%; 1.5%. Flavonoid content were measured by densitometry. Observation result of physical stability such as latched power, viscosity test, and flavonoid content were statistically analyzed. Result of formula orientation showed that lotion which has 1% concentration of xanthan gum was the best which has latched power less than 1 second, viscosity increased weekly, and segregation was not occur. Type of emulsion result was o/w. Densitometry result showed that there were decrease of relative flavonoid ontent before and after storage, but it was not significant (α = 0.58).